15*5*3x+3=-1*3*5*15

Simple and best practice solution for 15*5*3x+3=-1*3*5*15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15*5*3x+3=-1*3*5*15 equation:


Simplifying
15 * 5 * 3x + 3 = -1 * 3 * 5 * 15

Multiply 15 * 5
75 * 3x + 3 = -1 * 3 * 5 * 15

Multiply 75 * 3
225x + 3 = -1 * 3 * 5 * 15

Reorder the terms:
3 + 225x = -1 * 3 * 5 * 15

Multiply -1 * 3
3 + 225x = -3 * 5 * 15

Multiply -3 * 5
3 + 225x = -15 * 15

Multiply -15 * 15
3 + 225x = -225

Solving
3 + 225x = -225

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 225x = -225 + -3

Combine like terms: 3 + -3 = 0
0 + 225x = -225 + -3
225x = -225 + -3

Combine like terms: -225 + -3 = -228
225x = -228

Divide each side by '225'.
x = -1.013333333

Simplifying
x = -1.013333333

See similar equations:

| 4.9=2x+2.3 | | 3X-4(-3X-7)=13 | | (4r-2)=12 | | f-9=2 | | -(3z-4)= | | 3-2=2-5 | | 3y+5+2y-7=153 | | 3x+1=1x+13 | | 8x^2-12x-4=0 | | 5x^2=210x | | g-2y=9 | | y-12=-2x-2 | | -2y+x=9 | | 7-5x=-8(6+2x) | | -3x+10x= | | 3(4-2x)=-2(4x-1) | | -6(-2-2g)= | | 5x+2X-3= | | 4x+y^2=12 | | 2a+4-8a-19= | | -18-6= | | 2(6m+8)= | | 6(10+10g)+2= | | z+(-7)=-5 | | 2ln(x+1)=ln(1-2x) | | .42-1.2=.3r+.6 | | X+11=3x+31 | | 2h=d | | 2(1+8a)+8a= | | 3x-35=125 | | w+6=-9 | | 9m-3m(m+6)=2(m+1) |

Equations solver categories